Inner engineering is associated with perceived improvements in relationship quality, interpersonal connections, and interpersonal compassion - Jafari, Nashaw; Manvelian, Atina; Mohamed, Enas; Rayapuraju, Akila; Orui, Hibiki; Alkuhaimi, Sultan; Reed, Preeti Upadhyay; Subramaniam, Balachundhar (Frontiers in Psychology, 2024)
ObjectivesInterpersonal relationships are a cornerstone of wellbeing. Mindfulness-based practices have been shown to improve relationship quality and reduce perceived stress. Inner Engineering (IE) is a transformative program that includes meditative and yogic practices associated with improvements in mindfulness and wellbeing.MethodsThis cross-sectional observational study enrolled participants who were already registered for the Inner Engineering program to learn Shambhavi Mahamudra Kriya, a multi-component, 21-min meditation. Of the 356 participants who consented, 290 participants downloaded the mobile 3Cs app to participate. The enrolled participants were asked to complete self-reported electronic questionnaires at three timepoints: before the program, post-program, and 6 weeks after the program. The following measures were used: the Positive-Negative Relationship Quality (PN-RQ) scale, Interpersonal Mindfulness Scale (IMS), Perceived Stress Scale (PSS), Compassion Scale (CS), and Flourishing Measure. Linear mixed-effects models were used to analyze the survey data, with p-values of < 0.05 considered statistically significant.ResultsFrom the baseline to the 6-week follow-up after the program, the participants reported experiencing more positive qualities (p < 0.001, ηp2 = 0.12) and fewer negative qualities (p = 0.001, ηp2 = 0.08) in their relationships, increased interpersonal mindfulness (p < 0.001, ηp2 = 0.30), decreased stress levels (p < 0.001, ηp2 = 0.27), enhanced compassion for others (p < 0.001, ηp2 = 0.17), and overall personal wellbeing (p < 0.001, ηp2 = 0.25).ConclusionParticipation in the Inner Engineering yoga program appears to be associated with improvements in relationships, interpersonal mindfulness, compassion, stress, and overall wellbeing.Clinical trial registrationClinicalTrials.gov, identifier: NCT05528978.